2017
DOI: 10.1007/s12032-017-1065-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of venous thromboembolism in newly diagnosed patients treated for lymphoid malignancies: validation of the Khorana Risk Score

Abstract: The utility of the venous thromboembolism (VTE) risk assessment model known as the Khorana Risk Score (KRS) in patients with lymphoid malignancies receiving outpatient chemotherapy is not defined. We evaluated the association of the KRS with VTE in patients treated for diffuse large B cell lymphoma (DLBCL) or Hodgkin lymphoma (HL). Retrospective analyses were performed in 428 patients, 241 of whom were newly diagnosed with DLBCL and 187 of whom had HL. During the initial therapy, 64 (15%) patients developed VT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 43 publications
(47 reference statements)
6
33
1
1
Order By: Relevance
“…[13][14][15][16]36,37 This is further supported by our study in which the KRS did not adequately predict VTE events in patients at a higher risk of VTE in a cohort of patients with lymphoid malignancies. 37 Therefore, Antic et al developed the prognostic Thrombosis Lymphoma (ThroLy) score which is more specific for lymphoma patients than any other available scores targeting thrombosis in cancer patients. 19 Although the ThroLy model has been evaluated in both an initial derivation and a validation cohort, it has not been externally evaluated yet.…”
Section: Discussionmentioning
confidence: 51%
“…[13][14][15][16]36,37 This is further supported by our study in which the KRS did not adequately predict VTE events in patients at a higher risk of VTE in a cohort of patients with lymphoid malignancies. 37 Therefore, Antic et al developed the prognostic Thrombosis Lymphoma (ThroLy) score which is more specific for lymphoma patients than any other available scores targeting thrombosis in cancer patients. 19 Although the ThroLy model has been evaluated in both an initial derivation and a validation cohort, it has not been externally evaluated yet.…”
Section: Discussionmentioning
confidence: 51%
“…For example, the Khorana risk score for determining the risk of VTE in patients with cancer categorizes all patients with NHL in a high‐risk category . Because only a small proportion of the patients (12.8%) had NHL in this study, the utility of the Khorana score in lymphoid malignancies has been questioned . A majority of the subsequent VTE risk assessment models for patients with lymphoma have had poor clinical utility because of low discriminatory performance .…”
Section: Discussionmentioning
confidence: 99%
“…11 Because only a small proportion of the patients (12.8%) had NHL in this study, the utility of the Khorana score in lymphoid malignancies has been questioned. 12,13 A majority of the subsequent VTE risk assessment models for patients with lymphoma have had poor clinical utility because of low discriminatory performance. 14 development of neutropenia during therapy, and a hemoglobin level <10 g/dL increased the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…and V.D.S.). Of the 25 studies included, 12 studies were retrospective single-center studies [7,8,[10][11][12][13][14][15][16][17][18][19], two studies were retrospective multicenter trials [20,21], two pooled analysis of clinical trials [9,22], two meta-analyses [23,24], two analyses of patients [25,26] and three analyses of population-based registries [27][28][29], and two prospective single-center studies [6,30] ( Table 1). Four additional studies were identified by cross-referencing in the 21 published reports.…”
Section: Methodsmentioning
confidence: 99%